2020
DOI: 10.2196/preprints.22068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topics, Delivery Modes, and Social-Epistemological Dimensions of Web-Based Information for Patients Undergoing Renal Transplant and Living Donors During the COVID-19 Pandemic: Content Analysis (Preprint)

Abstract: BACKGROUND

The COVID-19 pandemic has markedly affected renal transplant care. At times of social distancing, limited in-person visits, and confronting uncertainties, patients and donors rely more than ever on telemedicine and online information. Several factors could influence patients’ understanding of online information, such as delivery modes (instruction, interaction, and assessment) and social-epistemological dimensions (choices in intera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…ODL is a new mode for traditional IHE, and the greatest challenge for educators is how to prevent passive learning in online education; and when the curriculum has not been designed for this mode (Malhotra, 2020), the authors think that this could increase the risk that students may lose interest in the content. Van Klaveren et al (2020) found that the majority of online delivery modes during the COVID-19 pandemic focused on passive learning. Passive learning “may limit students’ thinking, problem solving abilities, and motivation for learning” (Healy and Smyth, 2017, p. 44).…”
Section: Discussionmentioning
confidence: 99%
“…ODL is a new mode for traditional IHE, and the greatest challenge for educators is how to prevent passive learning in online education; and when the curriculum has not been designed for this mode (Malhotra, 2020), the authors think that this could increase the risk that students may lose interest in the content. Van Klaveren et al (2020) found that the majority of online delivery modes during the COVID-19 pandemic focused on passive learning. Passive learning “may limit students’ thinking, problem solving abilities, and motivation for learning” (Healy and Smyth, 2017, p. 44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the employment of mobile health technology application aimed at managing and monitoring medication for KTR has proved useful for these patients [20]. However, it seems that the quality of online information for transplant health care still needs improvements [21]. A recent clinical trial has shown that a web-based intervention with individual telemedicine couching for three months was able to cause reduction in dietary sodium in CKD patients, including KTR, when compared to regular routine care [22].…”
mentioning
confidence: 99%